Water Utility Turnaround Framework : A Guide for Improving Performance - Soppe, Gerhard (World Bank, Washington, DC, 2018)
In many urban areas around the world, public utilities provide water supply and sanitation (WSS) services. While some of these urban public water and sanitation utilities ("water utilities") perform well, others suffer from the types of performance issues observed in many public sector entities, such as low operating and investment efficiency. A framework for turning around poorly performing water utilities will benefit the management of these utilities, governments with responsibilities for water utilities, and those providing technical and financial support for improving the WSS sector. Improving the performance of water utilities is difficult because the problems they face are complex and multidimensional. Problems caused by dysfunctional political environments, combined with an entrenched backlog of inefficient practices, cannot be solved by applying standard technical and managerial techniques. Achieving a sustained turnaround requires a framework that integrates practical steps to increase a utility's operational and managerial efficiency with measures to reverse the dysfunctional political equilibria in which it operates. Using a comprehensive turnaround framework is the best approach to improve water utilities' performance and efficiency, and increase their ability to access finance, including commercial finance. Why does this matter? Evidence shows that water utilities with access to commercial finance are much more likely to achieve the Sustainable Development Goals.